Cough and upper airway disorders in elite athletes: a critical review - Boulet, L. P. (British Journal of Sports Medicine, 2012)
Respiratory diseases such as asthma, chronic cough, recurrent respiratory infections and various upper airways conditions are common in elite athletes, but these conditions are often underdiagnosed and undertreated. Recurrent cough, often observed after exercise, is the most commonly reported symptom in athletes, particularly winter athletes, but it does not predict airway function; its intensity correlates with the dryness of inspired air but may not be associated with airway hyper-responsiveness. Rhinitis, either allergic or not, is highly prevalent in athletes, particularly non-allergic rhinitis in swimmers. Finally, dysfunctional breathing, including vocal cord dysfunction, may mimic or accompany asthma in a significant number of athletes. These conditions should be recognised and treated properly according to current guidelines, although how these last apply in the athlete is uncertain. Furthermore, regulatory agencies' restrictions on the type of drugs allowed for therapeutic use of these conditions in competitive athletes should be checked.